STRATEGI PENGEMBANGAN PRODUK DESA DAYEUHLUHUR MENUJU DESA WISATA - Paramita, Rida Kania; Putra, Gilang Pratama; Supriyadi, Tedi (Jurnal Pariwisata PaRAMA : Panorama, Recreation, Accomodation, Merchandise, Accessbility, 2025)
The development of tourist villages can serve as an effort to achieve equitable development at the village level across various regions in Indonesia. This, in turn, is expected to improve the local economy and promote the preservation of culture, the environment, and local wisdom. This study explores the potential of Dayeuhluhur Village as a Tourist Village and the strategies for its development. The research employs a qualitative design with an exploratory case study approach. Data collection was conducted through interviews involving 10 key informants. An tematic data analysis was carried out to identify, evaluate, and generate themes from the informants' perspectives using Nvivo 12 software. Triangulation methods were used to validate both instruments and data. The study identified five key findings: the potential of Sumedang as a Tourist Village, the potential of Dayeuhluhur as a Tourist Village, the development of Dayeuhluhur Village towards becoming a Tourist Village, promotional efforts, and development strategies. This research contributes by identifying strategies through a SWOT analysis